2005
DOI: 10.2170/jjphysiol.r2096
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Enhances Tumor Necrosis Factor-α–Induced Expressions of Anti-Apoptotic Genes without Alterations in Caspase-3 Activity in Rat Epididymal Adipocytes

Abstract: ABSTRACT:The effect of exercise training on tumor necrosis factor-α (TNF-α) signaling was investigated in rat epididymal adipocytes. Incubation of isolated adipocytes with TNF-α (20 ng/ml) for 5 h enhanced the expression of the inhibitor apoptosis protein 2 (IAP2) gene without any enhancement of caspase-3 activity in both the sedentary control (C) and exercise-trained (TR) groups. However, the ability of TNF-α to enhance IAP2 gene expression was significantly greater in TR than in C rats. The basal expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…There is strong evidence for regular exercise can decrease the expression and levels of TNF-α in people with obese and insulin resistance [11]. These observations were paralleled by similar findings in rodent [12]. It has been demonstrated that increased expression of inflammation-related markers results in the increased HOAW-IR index.…”
Section: Insulin Sensitivitymentioning
confidence: 56%
See 2 more Smart Citations
“…There is strong evidence for regular exercise can decrease the expression and levels of TNF-α in people with obese and insulin resistance [11]. These observations were paralleled by similar findings in rodent [12]. It has been demonstrated that increased expression of inflammation-related markers results in the increased HOAW-IR index.…”
Section: Insulin Sensitivitymentioning
confidence: 56%
“…Based on this, increased oxidative stress in adipocytes is one of the causes of insulin resistance. However, the regular exercise has long been valued for its benefits of reduction in oxidative stress, research has found that manganese-containing SOD (Mn-SOD) levels in adipocytes are significantly greater in exercise-trained rats compared with those in untrained rats [12], this result suggest that exercise may decreased the oxidative stress via the increased antioxidative enzymes activity in adipocyte. Recently a study has found that ROS generated during exercise act as signals to increase the production of enzymes relevant to adaptation of muscle cells to exercise [38].…”
Section: Exercise Oxidative Stress and Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased expression of TNF- α in visceral WAT in mice that became obese after six weeks of consuming a high-fat diet can be suppressed by spontaneous running [25, 26]. Additionally, our studies showed that nine weeks of treadmill running decreased the TNF- α protein content of the rat WAT [27, 28], but some results have shown a contrasting increase after TR [24, 29, 30]. Studies regarding obese individuals have also examined the effects of TR on TNF- α expression in WAT.…”
Section: Representative Adipokines and The Effects Of Trmentioning
confidence: 99%
“…Adipocytes have produced reactive oxygen, and obesity-induced increases in oxidative stress in WAT may be a cause of the dysregulated expression of inflammatory-related adipokines [88]. Studies have shown significantly lower levels of lipid peroxidation in WAT around the epididymis and retroperitoneum of rats that had undergone TR compared with a control group, and elevated protein levels of the antioxidant enzyme manganese superoxide dismutase (Mn-SOD) in the epididymal WAT of TR group rats [27, 28]. In that study, not only were protein levels of TNF- α and MCP-1 significantly lower in the epididymal WAT of the TR group, compared with those of the control group, the phosphorylation of extracellular signal-regulated kinase, which is activated by reactive oxygen and is important for the expression of MCP-1, also was reduced by TR in WAT around the epididymis and retroperitoneum [27, 89].…”
Section: The Relationship Between Tr-induced Changes In Adipokine mentioning
confidence: 99%